HPV-associated Oropharyngeal Cancer: A Distinct Clinical Entity - Hughes, Katherine (Trinity Student Medical Journal, 2018)
It is now widely accepted that cervical cancer cannot develop in the absence of Human papillomavirus (HPV) infection. Less well known is the link between HPV and oropharyngeal cancer (OPC). With falling smoking rates, OPC rates were expected to decline. However this has not occurred, potentially due to a rise in HPV-associated OPC. This literature review aims to provide a summary of the most recent data regarding risk factors, biomarkers and prognosis for HPV-positive OPC, and to compare these findings with HPV-negative OPC. In light of its improved prognosis, this paper will also discuss the potential merits of treatment de-escalation in cases of HPV-positive OPC. A search was carried out on PubMed with the keywords Human papillomavirus, oropharyngeal cancer, and head and neck cancer. The search focused on papers published in the past 5 years but did not exclude seminal or relevant studies published earlier. Conclusion: HPV-associated oropharyngeal cancer should be recognised as a distinct clinical entity, which stands in contrast to HPV-negative OPC with regards to its aetiology, risk factors, chemotherapy and radiation therapy sensitivity and therefore also prognosis. More research is required to determine appropriate treatment and public health strategies.